Lingbe as aMedia against Speaking Anxiety for German Language Learning - Anky, Kianti Athavania Putri; Afifah, Lilis (Universitas Negeri Malang, 2022)
Speaking is an important skill in german language. Yet, speaking anxiety is a continuous topic in foreign language learning. Media learning has inovated futher to address the issue of language learning especially speaking. One of the innovated media learning platform is an app called Lingbe. Lingbe is a language exchange application by which language learners can have a call with natives. The purposes of this research were to describe the students’ activities using Lingbe on students of German Department in State University of Malang towards their language speaking anxiety and to describe the students’ responses about the implementation of the app. This research used qualitative approach with descriptive research type. The data were collected using observation, questionnaire, and interview technique. The result shows that the implementation of Lingbe run well after going through three meetings as planned. Students reveal that they are interested to use it periodically to help them by practicing their speaking skill and to lessen their anxiety of speaking German. Furthermore, students feel comfortable to have conversations with natives by using this apps.